THE PROGNOSIS OF RAIL PASSENGER TRANSPORT PERFORMANCES THROUGH CAUSUAL MODELS (Perner's Contacts, 2009)
Nowadays the transport companies use the prognosis of rail passenger transport performances especially in planning processes. The prognosis is possible to formate on the basis of mathematic–statistical models whereas their results can be very different in dependence on applied model. In the paper there is constructed prognosis of rail passenger transport performances for a short term with the aid of single regressive models and multiply linear regressive model. The paper deals with the comparison results of these models and their interpretation for transport practice.
Keywords: prognosis; passenger railway transport; regressive model; verification of model